Gaya Pengambilan Keputusan Pembelian Pakaian Secara Online pada Generasi Z Indonesia - Giovani Santoso; Anna Triwijayati (Jurnal Ilmu Keluarga dan Konsumen, 2018)
Strategic marketing decisions are based on the way the company understands consumers, including the wayconsumers make purchasing decisions. This study aimed to analyze the generation Z consumer decision-makingstyle in Indonesia in the purchasing of clothing by online shop media. Generation Z is a generation that is differentfrom the previous generation because it has a unique character and has technological literacy. In this reseach thedecision-making style used eight factors from the Consumer Style Inventory (CSI). Samples of research were 200people generation 16-22 years old who have bought clothes in online shop. The sampling technique usedpurposive sampling. Data analysis technique used the Confirmatory Factor Analysis. The results showed thatseven factors that were brand consciousness, perfectionist, high-quality consciousness, recreational, hedonisticconsumer, impulsiveness, confused by over choice, fashion-conscious novelty, and habitual and brand loyalorientation found in Indonesian Z generation in purchasing clothes by online. Another factor was that the pricevalue of consciousness is not confirmed in this study. Understanding consumer decision-making styles canexplain the basic considerations of Z generation as young consumers when choosing products from severalalternative product choices, brand selection, online stores, and purchasing intentions.